Effectiveness of mental training to increase self-efficacy and reduce competition anxiety in athletes - Prima Aulia; Dwi Puspasari; Tania Fajrika; Yoli Firda Salfina (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This research aims (1) to see the effectiveness of mental training in increasing self-efficacy, and (2) reducing competition anxiety among taekwondo athletes in West Sumatera Province. This research used quasi-experimental method with one group pretest-posttest research design which involved 20 subjects, 10 subjects conducted in Dojang HTC Fighter to measure self-efficacy and another 10 subjects to measure competition anxiety from Dojang Kodim Bukittinggi. The data were collected using a self-efficacy scale and a competition anxiety scale, to test the quality of the instrument a content validity test was used with professional judgement, while to see the reliability of the instrument using SPSS 19.0 for Windows with the Alpha Cronbach technique. The self-efficacy scale consists of 27 items with an alpha coefficient of (α) 0.925 and the competing anxiety scale consists of 12 items with a reliability coefficient value on the aspect of cognitive anxiety of 0.81, and somatic anxiety of 0.82. The research results show that the use of mental training is effective in increasing self-efficacy and reducing competition anxiety in taekwondo athletes.